1985
DOI: 10.1126/science.3872478
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Stimulation of Astroglial Proliferation After Brain Injury

Abstract: The interleukins, which have a regulatory role in immune function, may also mediate inflammation associated with injury to the brain. In experiments to determine the effect of these peptide hormones on glial cell proliferation in culture, interleukin-1 was a potent mitogen for astroglia but had no effect on oligodendroglia. Interleukin-2 did not alter the growth of either type of glial cell. Activity similar to that of interleukin-1 was detected in brains of adult rats 10 days after the brains had been injured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
307
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 829 publications
(323 citation statements)
references
References 19 publications
16
307
0
Order By: Relevance
“…It has been reported that astrocytes produce IL-1 [37] and IL-1 stimulates the proliferation of astrocytes [38]. Our results suggest that IL-1 induces the production of several cytokines and glucocorticoids regulate their production negatively in astrocytes.…”
Section: ~Bsupporting
confidence: 56%
“…It has been reported that astrocytes produce IL-1 [37] and IL-1 stimulates the proliferation of astrocytes [38]. Our results suggest that IL-1 induces the production of several cytokines and glucocorticoids regulate their production negatively in astrocytes.…”
Section: ~Bsupporting
confidence: 56%
“…Degeneration of severed axon tracts appears to lead to gliosis, even in regions remote from the site of trauma in the brain or spinal cord (Barrett et al, 1981;Fitch and Silver, 1997a;Massey, et al, 2006;Murray et al, 1990;Steward and Trimmer, 1997). Cytokines or other molecules that may trigger gliosis include TNF-alpha (Rostworowski et al, 1997), endothelin-1 (Hama et al, 1997), IL-1 (Giulian and Lachman, 1985), IL-6 (Chiang et al, 1994), thrombin (Nishino et al, 1993), and CNTF (Kahn et al, 1995). Some of these may originate as soluble serum factors, or they can be directly produced by astrocytes, activated microglia, or peripheral macrophages.…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
“…A number of diverse stimuli have been shown to induce astrocyte hyperplasia or hypertrophy, in cluding cytokines (Fontana et aI., 1980;Merrill et aI., 1984;Guilian and Lachman, 1985), brain derived glial growth factors (Sheffield and Kim, 1977;Pruss et aI. , 1982;Lemke and Brockes, 1984;Guilian and Young, 1986), epidermal growth factors (Brunk et aI.…”
Section: Discussionmentioning
confidence: 99%